Factors Behind Consumer Purchases: The Influence of Price, Product Quality, and Promotion at Master Acc Store Pekanbaru - Nanda Suryadi; Yayu Kusdiana; Arie Yusnelly; Nurul Dita Cahyani (International Conference on Business Management and Accounting, 2025)
This study aims to examine the effect of price, product quality, and promotion on purchase decisions at Master Store Acc Pekanbaru, with a sample of 64 respondents. Data were analyzed using multiple linear regression, hypothesis testing, and the coefficient of determination via SPSS 25.The results indicate that price and promotion have a partial effect on purchase decisions, while product quality does not. Simultaneously, all three variables significantly influence purchase decisions, with an Adjusted R Square of 0.734, meaning that 73.4% of purchase decision variation can be explained by these variables.